PIC robotics a beginner's guide to robotics projects using the PICmicro - Iovine, John (McGraw-Hill, 2004)
In this heavily-illustrated resource, author John Iovine provides plans and complete parts lists for 11 easy-to-build robots each with a PICMicro "brain." The expertly written coverage of the PIC Basic Computer makes programming a snap -- and lots of fun.